Code, but no ethics. (Economist, 2004)
This article reports on the multiple security problems being faced by Microsoft. Hardly a week now goes by without another security crisis for Windows, Microsoft's ubiquitous operating system. With the MyDoom virus--the fastest-spreading ever--finally in remission, Microsoft announced the discovery of another embarrassing software flaw. Adding insult to injury, another geek with a dislike for Microsoft leaked on to the internet millions of lines of the source code that underlies two versions of Windows. The real embarrassment is that each new incident invites more unfavourable comparisons between Microsoft and its chief rival, Linux. Microsoft argues that this is only because Linux is a smaller target and thus gets attacked less. The Linux camp counters that their operating system itself is safer, thanks to the way in which it is written.